Interactive Learning Media Application For The Introduction Of Human Needs In Children Aged - Vany Teresia; Lie Jie; Cai Jixiong (Yayasan Adra Karima Hubbi, 2023)
Early childhood education is a form of education that focuses on establishing the basis for significant physical growth and development, such as body growth and motor development. Children begin to develop the ability to think, learn, remember and understand basic concepts. This research aims to produce an animated application for the introduction of human needs in children for their congnitive development. In the design process using Flowchart diagram to create an overview of how the process in the interactive learning media application. Storyboard is used for an overview of the appearance and workings of interactive learning media applications. There are several choices of materials such as food, drink, clothing, health, hygiene and safety. All materials are equipped with sound images and attractive displays. Flowchart is used to display the workflow, from the start to the stage of selecting interactive learning media application materials. The application contains material that already covers the curriculum used by PAUD schools in general. Interactive learning media applications help early childhood in learning about human needs.